The Effect of Long-Term Proton Pump Inhibitor Use on FrailtySyndrome in Elderly Patients - Dewi, Stephanie; Laksmi, Purwita W.; Syam, Ari Fahrial (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Frailty syndrome, the newest elderly health predictor, associated with higher morbidity and mortality. PPI are often used in elderly due to presence of upper gastrointestinal complaints, and relates with polypharmacy as one of the risk factor for frailty syndrome. There is no study of the relationship between long term PPI use and frailty syndrome in elderly. Methods. A case control study included subjects 60 years and above with good cognitive status. All subjects with history of hypersensitivity of PPI were excluded. Elderly who were frail based on FI-40 item were defined as cases, while individuals that were not frail were classified as control. Primary data (included frailty status) was collected on March-June 2013 by Seto E and Sumantri S, et al. Secondary data used in this current study were gathered from the primary data of previous research and from the medical record taken from geriatric and diabetic outpatient clinics Cipto Mangunkusumo Hospital. Results. There were 225 subjects collected (75 cases: 150 controls), 59,6% were female (mean age 72,14 years old, SD ± 6,4 years) and 47,1% with higher education. Lower education, divorced, poor nutrition, dependent, needed caregiver, economically insufficient, more comorbidity and poor health condition were seen in frail group. The proportion of long term PPI use were 40,9%. Long term PPI medication increased the risk of frailty syndrome (Crude OR 2,154; CI 95% 1,225-3,778; p<0,007) with adjusted OR 1,83 (CI 95% 1,02-3,37) after adjusting with nutrition and smoking variables. Conclusions. Long term use of PPI significantly increase the risk of frailty syndrome compared to the non-users.